Hi,

First let me say that I am not looking for the answer, just a few hints to help me get started. I want to make sure I understand this as much as possible.

The problem states for me to identify the error in the proof:

Let u, m, n be three integers. If u|mn and gcd(u,m) = 1, then m = +- 1. If gcd(u,m ) = 1, then 1 = us + mt for some integers s,t. If u|mn, then us = um for some integer s. Hence, 1 = mn + mt = m(s + t), which implies that m|1, and therefor m = +- 1.

Thanks for any help,

Tony